PENGARUH PRESEPSI HARGA, KUALITAS PELAYANAN, DAN KUALITAS PRODUK SENDAL TERHADAP KEPUASAN PELANGGAN DI UD. SAMPUN MAPAN DI PASAR KRIAN - Fidia Suci Ratnasari; Mukti Ali (Jurnal Ekonomi dan Bisnis, 2024)
UD. Sampun Mapan is a trading business located in Krian Market, Sidoarjo Regency with products in the form of sandals. UD. Sampun Mapan managed to dominate sales. Consumers think that the price, service and product quality offered are very satisfying. This study aims to determine whether the perception of price, service and product quality has a positive and significant impact on customer satisfaction so that UD. Sampun Mapan can dominate sales. Collecting data in this study used a survey method with a total sample of 100 people and processed with SPSS.25. The results of the research with descriptive analysis show that the value for customer satisfaction is 81.4% and is included in the "High" category. For the results of the quantitative analysis, based on partial testing the value for the price variable is Tcount 2.576 > Ttable 1.98498 and a significance value of 0.012 <0.05, the value for the service variable is Tcount 2.378 > Ttable 1.98498 and a significance value of 0.019 <0.05 and the value for the product quality variable is Tcount 6.380 > Ttable 1.98498 and a significance value of 0.000 <0.05. Of the three results This shows that the three variables have a positive and significant influence on customer satisfaction variables. For simultaneous testing, the result is that all variables together have a significant effect on customer satisfaction.